Estimation of CO2 emission factors of coals - (:unkn) unknown (ELSEVIER SCI LTD, 1998)
New formulae have been developed to estimate CO2 emission potentials of coals from easily obtainable coal properties such as heating value, volatile matter and fixed carbon contents. The magnitude of CO2 emission per unit amount of coal combusted as well as per unit amount of coal heating value were selected as CO2 emission potential indicators of coals. Within this frame proximate, ultimate and calorific value analysis results of 39 Turkish coals with widely varying rank characteristics were evaluated via regression analyses. Simple formulae with mean differences less than 3% were obtained. Published data of 122 coals from abroad were used to check some of the developed formulae and to search for less erroneous correlations. (C) 1998 Elsevier,Science Ltd All rights reserved.
Keywords: coal; combustion; CO2 emission factor; correlations